2015
DOI: 10.1016/j.nbd.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between iron dyshomeostasis and amyloidogenesis in Alzheimer's disease: Two sides of the same coin

Abstract: The dysregulation of iron metabolism in Alzheimer’s disease is not accounted for in the current framework of the amyloid cascade hypothesis. Accumulating evidence suggests that impaired iron homeostasis is an early event in Alzheimer’s disease progression. Iron dyshomeostasis leads to a loss of function in several enzymes requiring iron as a cofactor, the formation of toxic oxidative species, and the elevated production of beta-amyloid proteins. Several common genetic polymorphisms that cause increased iron le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 256 publications
3
70
0
1
Order By: Relevance
“…The accumulation of these pathologies leads to disruption of iron homeostasis (Peters, et al, 2015) and increased free water content due to demyelination and atrophy (Zhan, et al, 2015). These changes in brain tissue properties can be detected by using magnetic resonance imaging (MRI) relaxometry, both in vivo and ex vivo .…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of these pathologies leads to disruption of iron homeostasis (Peters, et al, 2015) and increased free water content due to demyelination and atrophy (Zhan, et al, 2015). These changes in brain tissue properties can be detected by using magnetic resonance imaging (MRI) relaxometry, both in vivo and ex vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In several other neurodegenerative disorders including AD, PD, HD, amyotrophic lateral sclerosis, multiple sclerosis, and Friedreich's ataxia, loss of iron homeostasis, oxidative stress, and mitochondrial injury have been suggested to constitute a common pathway to cell death although the pathological hallmarks of these neurodegenerative diseases vary. Currently, a key question of why iron increases abnormally in some brain regions of these diseases has not been answered.…”
Section: Brain Iron Misregulation Is a Common Pathway In Neurodegenermentioning
confidence: 99%
“…AD patients have abnormal iron distribution in cortical and subcortical areas including the hippocampus [136]. While total cortical iron levels may be unaltered in AD [137], post-mortem MRI and histopathological studies showed that increased iron levels are associated with amyloid-beta (Abeta) plaques [138,139], vessel walls, and microglia [140].…”
Section: Parkinson's and Alzheimer's Diseasesmentioning
confidence: 99%